Pelatihan Pembuatan Sabun Antiseptik Berbasis Minyak Biji Kelor pada Kelompok Wanita Tani Flamboyan Lingkar Pratama Lombok-Nusa Tenggara Barat - Sri Seno Handayani; Erin Ryantin Gunawan; Dedy Suhendra; Murniati Murniati; Dhony Hermanto (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
On the West Nusa Tenggara island of Lombok, a local plant called moringa (Moringa oleifera) is frequently found. Due to its high nutritional value, this plant can be consumed in almost all of its components, particularly the leaves and seeds. With the help of Flamboyan Women Farmers Group (Kelompok Wanita Tani Flamboyan) partners, this service activity was carried out by lecturing the public on the uses of moringa plants and other local flora as antiseptic soap and providing instruction on how to make soap from moringa seed oil. The activity's external advantages include: (1) enhancing farmer group mothers' knowledge of the advantages and potential of nearby plants; (2) facilitating the need for antiseptic soap for families; (3) enhancing mothers' motivation and creativity to create independent jobs in an effort to improve the family economy; and (4) producing publications in scientific journals. According to the outcomes of the community service projects, this training activity can improve the knowledge and skills of the women of the Flamboyan Farmers Group in the production of antibacterial soap using moringa seed oil.